2001
DOI: 10.1098/rspb.2001.1733
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of coral–dinoflagellate associations in Acropora : significance of local availability and physiology of Symbiodinium strains and host–symbiont selectivity

Abstract: Like other reef-building corals, members of the genus Acropora form obligate endosymbioses with dino£agellates (zooxanthellae) belonging to the genus Symbiodinium. Both Symbiodinium and its hosts are diverse assemblages, and the relationships between host and algal genotypes are unclear. In this study, we determined phylogenetic relationships between Symbiodinium isolates from a wide range of Acropora species and plotted the algal genotypes onto a molecular phylogeny of 28 Acropora species, using the same samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
317
3
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 292 publications
(330 citation statements)
references
References 23 publications
8
317
3
1
Order By: Relevance
“…Owing to differences in thermal tolerance, only Symbiodinium D (ITS1, sensu Van Oppen et al, 2001) are found in the warm pool, whereas both Symbiodinium C and D associate with corals in the cold pool, occasionally forming mixed assemblages within a colony.…”
Section: Methodsmentioning
confidence: 99%
“…Owing to differences in thermal tolerance, only Symbiodinium D (ITS1, sensu Van Oppen et al, 2001) are found in the warm pool, whereas both Symbiodinium C and D associate with corals in the cold pool, occasionally forming mixed assemblages within a colony.…”
Section: Methodsmentioning
confidence: 99%
“…Surveys of coral-algal symbioses from Western Australia can also be compared with similar latitudinal comparisons from other geographic regions (e.g. Baker 1999, Rodriguez-Lanetty et al 2001, van Oppen et al 2001, 2005, Savage et al 2002, Macdonald et al 2008, LaJeunesse et al 2010a) to corroborate hypothesized biogeographic patterns in the distribution of Symbiodinium diversity, and to determine where exceptions to these patterns arise, and why.…”
Section: Introductionmentioning
confidence: 99%
“…Cultures were maintained at 28 1C and 35 mmol quanta m À2 s À1 , under a 12:12 h light:-dark photoperiod. Cultures were genotyped by SSCP of the ITS1 region (van Oppen et al, 2001). Growth was monitored periodically by hemocytometry to estimate log phase time.…”
Section: Pathogenicity Testsmentioning
confidence: 99%